Effect of fluid pressure heterogeneity on injection-induced fracture activation - Ji, Yinlin (2021)
This study aims to understand the development of fluid pressure heterogeneity in a rock fracture and its influence on the injection-induced activation of the fracture. We first conduct injection-driven shear tests on a sawcut fracture close to a critical stress state using a triaxial shear-flow setup. The injection and monitoring pressures during the fluid injection are measured until the fracture is activated. We then use COMSOL multiphysics software to recover the fluid pressure distribution on the fracture based on the experimental data. When the degree of fluid pressure heterogeneity is low, the increase in fluid pressure on the fracture is nearly uniform, and the fluid pressure at fracture failure can be well predicted by the Mohr-Coulomb failure criterion. However, when the fluid pressure is highly heterogeneous, fracture rupture can be induced in the area with highly pressurized fluid, and propagates to activate the entire fracture. The fluid pressure at fracture failure is much higher than the predicted pressure, and increases with higher degree of fluid pressure heterogeneity.